2023
DOI: 10.1109/access.2023.3283436
|View full text |Cite
|
Sign up to set email alerts
|

Smart City Based on Open Data: A Survey

Karidja Dominique Christelle Adje,
Asma Ben Letaifa,
Majed Haddad
et al.

Abstract: Open data are gold mines because they can be used to create services that develop a smart city while improving users' living conditions. Several research works go in this direction, presenting open data impact in the smart city for some, while others have focused on data processing methods. We have therefore deemed it necessary to make a state of the art on these different issues. The particularity of our study is that it shows the link between open data and smart city in all its aspects, describing what kind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…In a research investigation, it was found that although all the portals in the GCC region are suitable for their purposes, they have some common weaknesses, such as the lack of advanced visualization tools and effective mechanisms for involving stakeholders in portal development. To enhance the assistance that portals can provide, it is suggested that they should more frequently use visualization tools and promote public awareness of common tools that can help in using open data [58]. Portal reliability is crucial in empowering citizens and improving their agreements and decisions with open data [59].…”
Section: Ensuring the Reliability Of Open Datamentioning
confidence: 99%
“…In a research investigation, it was found that although all the portals in the GCC region are suitable for their purposes, they have some common weaknesses, such as the lack of advanced visualization tools and effective mechanisms for involving stakeholders in portal development. To enhance the assistance that portals can provide, it is suggested that they should more frequently use visualization tools and promote public awareness of common tools that can help in using open data [58]. Portal reliability is crucial in empowering citizens and improving their agreements and decisions with open data [59].…”
Section: Ensuring the Reliability Of Open Datamentioning
confidence: 99%
“…The availability of open data allows researchers and developers to gather relevant and diverse data inputs for their machine learning models, enabling them to analyze and extract insights from large datasets [14]. However, using open data in ML applications also presents challenges, such as data quality, data format, and data integration from multiple sources [15]. The risks associated with open data, such as privacy concerns, data accuracy, and decision making based on faulty data, need to be assessed and mitigated [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, open data is crucial in enabling intelligent solutions, promoting sustainable and innovative urban environments, and propelling research in machine learning. It facilitates the creation of predictive models and decision-making tools tailored for smart city applications [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations